2017
DOI: 10.1055/s-0037-1607993
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Oral Anticoagulants for Intracerebral Hemorrhage Patients: Best Strategies

Abstract: In patients with acute intracerebral hemorrhage (ICH), one of the major concerns is ongoing bleeding or ICH expansion. Anticoagulated patients are at higher risk of ongoing expansion and worse outcome. It may be that rapid anticoagulation reversal can reduce the risk of expansion and improve clinical outcome. For those taking coumarins, the best available evidence suggests that intravenous vitamin K combined with four-factor prothrombin complex concentrate (4F-PCC) is the most rapid and effective regimen to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 108 publications
(97 reference statements)
0
4
0
1
Order By: Relevance
“…Several observational cohort studies found that 4F-PCC at a dose range of 25-50 units/kg achieves effective hemostasis in 65% to 94.7% of patients with oral FXa inhibitor-associated ICH. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Comparatively, excellent or good hemostasis was achieved in 80% of patients treated with andexanet alfa in the ANNEXA-4 trial, with a corresponding 92% reduction in apixaban and rivaroxaban levels after administration. 32 However, ANNEXA-4 exclusion criteria may not be representative of true clinical practice, as ethical considerations arise when restricting therapy from those with known risk factors for hematoma expansion, such as larger ICH volume or low GCS score at presentation, or low probability of survival at 30 days.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several observational cohort studies found that 4F-PCC at a dose range of 25-50 units/kg achieves effective hemostasis in 65% to 94.7% of patients with oral FXa inhibitor-associated ICH. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Comparatively, excellent or good hemostasis was achieved in 80% of patients treated with andexanet alfa in the ANNEXA-4 trial, with a corresponding 92% reduction in apixaban and rivaroxaban levels after administration. 32 However, ANNEXA-4 exclusion criteria may not be representative of true clinical practice, as ethical considerations arise when restricting therapy from those with known risk factors for hematoma expansion, such as larger ICH volume or low GCS score at presentation, or low probability of survival at 30 days.…”
Section: Discussionmentioning
confidence: 99%
“…Good or excellent hemostatic effectiveness was achieved in 88.9% of patients in the andexanet alfa cohort and 60% of patients in the 4F‐PCC cohort. Several observational cohort studies found that 4F‐PCC at a dose range of 25‐50 units/kg achieves effective hemostasis in 65% to 94.7% of patients with oral FXa inhibitor‐associated ICH 14‐29 . Comparatively, excellent or good hemostasis was achieved in 80% of patients treated with andexanet alfa in the ANNEXA‐4 trial, with a corresponding 92% reduction in apixaban and rivaroxaban levels after administration 32 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bu kanamalar cilt hematomu veya subkonjonktival kanama kliniğinde olabileceği gibi intraserebral veya epiglottik kanamalar gibi ciddi morbidite ve mortalite risklerini de beraberinde getirebilir. [4][5][6][7] Hifema, klinik pratiğimizde sıklıkla künt okü-ler travma sonucunda rastladığımız bir durum olmasına rağmen, nadiren warfarin gibi oral antikoagülan kullanımına bağlı, travma öyküsü olmaksızın da karşımıza çıkabilmektedir. Literatürde bu şekilde bildirilmiş olgu sayısı son derece sınırlı-dır.…”
unclassified